Stress-induced premature senescence in high five cell cultures: a principal factor in cell-density effects - Rui Min; Dahe Zhang; Mingzhe He; Jingyuan Chen; Xiaoping Yi; Yingping Zhuang (Bioresources and Bioprocessing)
Abstract The Baculovirus Expression Vector System (BEVS) is highly valued in vaccine development, protein engineering, and drug metabolism research due to its biosafety, operational convenience, rapid scalability, and capacity for self-assembling virus-like particles. However, increasing cell density at the time of inoculation severely compromises the production capacity of BEVS, resulting in the “cell density effect”. This study aimed to explore the mechanisms of the cell density effect through time-series analysis of transcriptomes and proteomes, with the goal of overcoming or alleviating the decline in productivity caused by increased cell density. The dynamic analysis of the omics of High Five cells under different CCI (cell density at infection) conditions showed that the impact of the “cell density effect” increased over time, particularly affecting genetic information processing, error repair, protein expression regulation, and material energy metabolism. Omics analysis of the growth stage of High Five cells showed that after 36 h of culture (cell density of about 1 × 106 cells/mL), the expression of ribosome-related proteins decreased, resulting in a rapid decrease in protein synthesis capacity, which was a key indicator of cell aging. Senescence verification experiments showed that cells began to show obvious early aging characteristics after 36 h, resulting in a decrease in the host cell’s ability to resist stress. Overexpression and siRNA inhibition studies showed that the ndufa12 gene was a potential regulatory target for restricting the “cell density effect”. Our results suggested that stress-induced premature senescence in High Five cell cultures, resulting in reduced energy metabolism and protein synthesis capabilities, was a critical factor contributing to cell density effects, and ultimately affecting virus production. In conclusion, this study provided new insights into managing virus production limitations due to cell density effects and offered innovative strategies to mitigate the adverse effects of cellular aging in biomanufacturing technologies. Graphical abstract